Perlindungan Pemerintah Daerah Terhadap Kelompok Minoritas “Towani Tolotang” di Sulawesi Selatan - Herman Lawelai (Universitas Pancasakti, 2020)
This article describes the efforts of the regional government to protect the Towani Tolotang people as a minority group in fighting for their identity, the argumentation of justice and group rights in the midst of a pluralistic culture. This article is analyzed with; historical agreements, equal rights, and cultural diversity. Using qualitative research methods, this study found that until now the minority group